ANALISIS KOPETENSI KEPRIBADIAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI KELAS IV SD NEGRI SUDIANG: ANALISIS KOPETENSI KEPRIBADIAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Mujdalifah, Siti; Syahid, Akhmad; Subaedah; Martini; Hasan, Salim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the role of teachers’ personality in improving students’ learning motivation in Mathematics for fourth-grade students at SD Negeri Sudiang. The focus of this research is to examine how teachers’ attitudes, personalities, and behaviors influence students’ enthusiasm for learning, as well as to identify the supporting and inhibiting factors in the process. This research employs a qualitative descriptive method with data collected through interviews, observations, and documentation. The results show that teachers’ personality plays a significant role in enhancing students’ learning motivation. Teachers who are patient, disciplined, and communicative are able to create an enjoyable and conducive learning atmosphere that increases students’ enthusiasm for Mathematics. However, challenges remain, such as students’ low interest in learning, teachers’ limited time due to administrative duties, and lack of family support. Therefore, improving students’ learning motivation requires collaboration among teachers, schools, and parents to build a positive and inspiring learning environment.